Is bone marrow oedema in patients with labral tear an indicator of hip pain? - Tomohisa Koyama; Kensuke Fukushima; Kentaro Uchida; Yoshihisa Ohashi; Katsufumi Uchiyama; Naonobu Takahira; Masashi Takaso (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background Hip labral tear (LT) causes various degrees of hip pain, for which there are few objective measures. Bone marrow oedema (BME), characterized by a diffuse, widely spreading change in the bone marrow, is observed in some patients with LT. However, its pathological role has not been fully understood. The purpose of this study was to investigate the prevalence of BME on hip magnetic resonance imaging (MRI) in patients with LT and to determine whether BME was an objective indicator of hip pain. Methods In total, 84 patients with LT who underwent MRI scanning under the same conditions were included. We determined the presence or absence of BME and its size on MRI and evaluated the relationships between BME and sex, age, and pain and total scores on the modified Harris hip score (MHHS). In addition, we collected data on surgical treatments such as hip arthroscopy within a one-year follow-up period and examined whether the presence of BME affected the course of therapy. Results BME was found in 34.5% of patients. MHHS pain and total scores were significantly lower in patients with BME (MHHS pain score: non-BME vs. BME ≤ 1 cm: p = 0.022, non-BME vs. BME > 1 cm: p < 0.001; MHHS total score: non-BME vs. BME ≤ 1 cm: p = 0.131, non-BME vs. BME > 1 cm: p = 0.027). The presence of BME did not differ between patients who did and did not undergo surgery during follow-up (p = 0.563). Conclusion BME on MRI in patients with LT might be an indicator of hip pain and hip joint dysfunction.